2022
DOI: 10.1093/hmg/ddac012
|View full text |Cite
|
Sign up to set email alerts
|

The variant rs77559646 associated with aggressive prostate cancer disrupts ANO7 mRNA splicing and protein expression

Abstract: Prostate cancer is among the most common cancers in men, with a large fraction of the individual risk attributable to heritable factors. A majority of the diagnosed cases does not lead to a lethal disease, and hence biological markers that can distinguish between indolent and fatal forms of the disease are of great importance for guiding treatment decisions. Although over 300 genetic variants are known to be associated with prostate cancer risk, few have been associated with the risk of an aggressive disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Our observations suggest that in the normal prostatic epithelium, ANO7 is expressed in luminal cells but not in basal cells, as the RNA-FISH signal was not detected in the basal layer of the epithelium ( Figure 2 D). Anti-ANO7 staining in both basal and luminal cells has been reported [ 19 , 28 ]. The antibody used in both of these studies, however, is not completely specific to ANO7 ( (accessed on 7 December 2022)), and the signal in basal cells was also observed in patients homozygous for a mutation that causes a severe splicing defect in ANO7 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our observations suggest that in the normal prostatic epithelium, ANO7 is expressed in luminal cells but not in basal cells, as the RNA-FISH signal was not detected in the basal layer of the epithelium ( Figure 2 D). Anti-ANO7 staining in both basal and luminal cells has been reported [ 19 , 28 ]. The antibody used in both of these studies, however, is not completely specific to ANO7 ( (accessed on 7 December 2022)), and the signal in basal cells was also observed in patients homozygous for a mutation that causes a severe splicing defect in ANO7 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-ANO7 staining in both basal and luminal cells has been reported [ 19 , 28 ]. The antibody used in both of these studies, however, is not completely specific to ANO7 ( (accessed on 7 December 2022)), and the signal in basal cells was also observed in patients homozygous for a mutation that causes a severe splicing defect in ANO7 [ 28 ]. Bera et al [ 7 ] concluded from in situ hybridization data that ANO7 mRNA is expressed in basal and terminal epithelial cells of the epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations